2019
DOI: 10.1002/ece3.4837
|View full text |Cite
|
Sign up to set email alerts
|

The integrative effects of behavior and morphology on amphibian movement

Abstract: Animal movement and dispersal are key factors in population dynamics and support complex ecosystem processes like cross‐boundary subsidies. Juvenile dispersal is an important mechanism for many species and often involves navigation in unfamiliar habitats. For species that metamorphose, such as amphibians, this transition from aquatic to terrestrial environments involves the growth and use of new morphological traits (e.g., legs). These traits strongly impact the fundamental ability of an organism to move in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Amphibian movement typically involves environmentally or resource‐directed movement between habitat patches that is often influenced by individual condition (e.g. condition‐dependent dispersal; Cayuela et al., 2020), thereby requiring a consideration of life history parameters to understand movement biology (Bowler & Benton, 2005; Bredeweg et al., 2019). Understanding the mechanisms underpinning movement is crucial in the management of populations and predicting population responses to environmental changes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibian movement typically involves environmentally or resource‐directed movement between habitat patches that is often influenced by individual condition (e.g. condition‐dependent dispersal; Cayuela et al., 2020), thereby requiring a consideration of life history parameters to understand movement biology (Bowler & Benton, 2005; Bredeweg et al., 2019). Understanding the mechanisms underpinning movement is crucial in the management of populations and predicting population responses to environmental changes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of biotic interactions in this context may help to explain why other studies of the experimental effects of drying on amphibian species have shown little or no negative impacts in the absence of other stressors (e.g., Amburgey et al 2012, Cook et al 2013). These results also suggest that drying alone may not be a significant stressor on larvae, but instead may manifest as latent effects on juveniles (Bredeweg et al 2019). Further, many of the measured responses in the interactive treatment involving three-species competition and drying were either the only significant effects for a species, or the responses were significantly different (and exacerbated) relative to those treatments involving single and pairwise competition.…”
Section: Discussionmentioning
confidence: 71%
“…These results also suggest that drying alone may not be a significant stressor on larvae, but instead may manifest as latent effects on juveniles (Bredeweg et al. ). Further, many of the measured responses in the interactive treatment involving three‐species competition and drying were either the only significant effects for a species, or the responses were significantly different (and exacerbated) relative to those treatments involving single and pairwise competition.…”
Section: Discussionmentioning
confidence: 89%
“…Locomotor ability is a good proxy for dispersal potential in amphibians (Denton et al., 2017; Yagi & Green, 2017). Size at metamorphosis influences locomotor ability, with smaller individuals (SVL and limb length) traveling shorter distances (Bredeweg et al., 2019), and sublethal effects of neonicotinoid pesticide exposure may further exacerbate these patterns. We found that aquatic exposure to sublethal concentrations of imidacloprid led to increased endurance of post‐metamorphic frogs at 18°C (Fig.…”
Section: Discussionmentioning
confidence: 99%